A nitrogen-rich ligand as a scaffold for slow magnetic relaxation in dysprosium-based 0D and 1D architectures. Issue 34 (19th February 2018) - Brunet, Gabriel; Sebastiao, Elena; Witkowski, Tomasz G.; Korobkov, Ilia; Gabidullin, Bulat; Murugesu, Muralee
Abstract : A nitrogen-rich ligand is employed as a scaffold for lanthanide ions, leading to clear SMM-like behaviour and two well-isolated modes of magnetic relaxation. Abstract : A recently designed nitrogen-rich ligand is successfully applied as a scaffold for lanthanide ions to show that the intricate chemistry of energetic materials can be combined with other fields of research, including that of molecular magnetism. Herein, we report the synthesis of two different types of molecular architectures using a single ligand template, in which the discrete monomer exhibits single-molecule magnet-like behaviour along with two well-isolated modes of magnetic relaxation.